Optimization of an Experimental Vaccine To Prevent Escherichia coli Urinary Tract Infection - Valerie S. Forsyth (American Society for Microbiology, 2020)
ABSTRACT Urinary tract infections (UTI) affect half of all women at least once during their lifetime. The rise in the numbers of extended-spectrum beta-lactamase-producing strains and the potential for carbapenem resistance within uropathogenic Escherichia coli (UPEC), the most common causative agent of UTI, create an urgent need for vaccine development. Intranasal immunization of mice with UPEC outer membrane iron receptors FyuA, Hma, IreA, and IutA, conjugated to cholera toxin, provides protection in the bladder or kidneys under conditions of challenge with UPEC strain CFT073 or strain 536. On the basis of these data, we sought to optimize the vaccination route (intramuscular, intranasal, or subcutaneous) in combination with adjuvants suitable for human use, including aluminum hydroxide gel (alum), monophosphoryl lipid A (MPLA), unmethylated CpG synthetic oligodeoxynucleotides (CpG), polyinosinic:polycytidylic acid (polyIC), and mutated heat-labile E. coli enterotoxin (dmLT). Mice intranasally vaccinated with dmLT-IutA and dmLT-Hma displayed significant reductions in bladder colonization (86-fold and 32-fold, respectively), with 40% to 42% of mice having no detectable CFU. Intranasal vaccination of mice with CpG-IutA and polyIC-IutA significantly reduced kidney colonization (131-fold) and urine CFU (22-fold), respectively. dmLT generated the most consistently robust antibody response in intranasally immunized mice, while MPLA and alum produced greater concentrations of antigen-specific serum IgG with intramuscular immunization. On the basis of these results, we conclude that intranasal administration of Hma or IutA formulated with dmLT adjuvant provides the greatest protection from UPEC UTI. This report advances our progress toward a vaccine against uncomplicated UTI, which will significantly improve the quality of life for women burdened by recurrent UTI and enable better antibiotic stewardship. IMPORTANCE Urinary tract infections (UTI) are among the most common bacterial infection in humans, affecting half of all women at least once during their lifetimes. The rise in antibiotic resistance and health care costs emphasizes the need to develop a vaccine against the most common UTI pathogen, Escherichia coli. Vaccinating mice intranasally with a detoxified heat-labile enterotoxin and two surface-exposed receptors, Hma or IutA, significantly reduced bacterial burden in the bladder. This work highlights progress in the development of a UTI vaccine formulated with adjuvants suitable for human use and antigens that encode outer membrane iron receptors required for infection in the iron-limited urinary tract.